Feminizing adrenocortical carcinoma in a postmenopausal woman. Issue 644 (June 1979) - Barcelo, B.; Abascal, J.; Ardaiz, J.; Gil, P.; Colas, A.; Menendez, J.; Inchausti, J. L.
Abstract : The successful surgical removal of a feminizing adrenal tumour in a postmenopausal woman is described. Most of these tumours are malignant and the pathological findings and the biological behaviour of the tumour frequently do not correlate, so that a careful follow-up is necessary. In the presence of vaginal bleeding in a postmenopausal woman endometrial carcinoma should be considered. If this has been ruled out and if oestrogens are elevated with low plasma gonadotrophins, a feminizing ovarian or adrenal tumour should be considered.